Implementasi Kebijakan Perpustakaan Universitas Indonesia dalam Pengembangan Koleksi Elektronik - Putri, Jasmine Anindita; Gani, Fuad (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2022)
Collection development policy is a guideline for libraries in developing collections. The University of Indonesia library experienced a budget reduction and a change in procedures during the COVID-19 pandemic. The purpose of this research is to identify what policies are taken by the University of Indonesia Library in the process of developing electronic collections. This study uses qualitative methods with data collection using interviews. Informants were determined by purposive sampling technique. The situation and conditions during the last five years have changed a lot. It also influences collection development policies. The policy was last revised in 2019. However, in 2020 Indonesia experienced a period of the COVID-19 pandemic which resulted in the library's condition changing due to the impact of COVID-19. The budget decline experienced by the University of Indonesia Library affected several collection development activities such as procurement and selection. The occurrence of a pandemic also led to changes in procedures for developing collections but these changes were not documented in writing. Therefore, the library needs to have written documents for the changes experienced during the budget decline and the pandemic.